Urban transition management as a democratic practice? The case of Rotterdam's waterfront Regeneration. - Jhagroe, Shivant (Springer, 2018)
This chapter examines the democratic aspects and challenges associated with urban transition management. It does so at a conceptual level and by critically reflecting on the application of transition management in the context Rotterdam's sustainable waterfront regeneration. As such, it aims to shed a more reflexive light on the increasing academic and public interest in transition management.
Keywords: Stadtentwicklung; Nachhaltige Stadtentwicklung; Hafengebiet; Binnenhafen; Stadterneuerung; Partizipation; Öffentlichkeitsbeteiligung; Bewohnerbeteiligung; Stadthafen